PROFIL BERPIKIR KREATIF SISWA KELAS VII SMP NEGERI 4 PALU DALAM MENYELESAIKAN SOAL CERITA PECAHAN DITINJAU DARI TIPE KEPRIBADIAN INTROVERT DAN EXTROVERT - Windawati; Baharuddin Paloloang; Sutji Rochaminah (Universitas Tadulako, 2021)
This study aims to describe the completion of fractional story problems for seventh grade students of SMP Negeri 4 Palu in terms of introvert and extrovert personality types. This type of research is a qualitative research with a qualitative descriptive approach based on indicators of creative thinking. The subjects in this study consisted of one student with an introverted personality, and one student with an extroverted personality.The results of this study indicate that: (1) Profi creative thinking students in solving fraction story problems with an introverted personality type (UA subject) obtained information that when UA reads questions repeatedly and understands questions it takes a long time to understand, UA provides a way of solving problems that are generally known by others , UA is not able to produce uniform ideas and different directions of thought, UA cannot provide unusual solutions that are rarely given by most people, UA is not able to develop, add, enrich an idea but solve problems in detail and can be understood by others. (2) Profi creative thinking of students in solving fraction story problems with extrovert personality type (subject BF) obtained information that BF reads the questions 2 times so that they can understand them, BF is able to provide more than one way of solving problems, namely three ways of solving based on the questions given by the researcher, BF was not able to produce uniform ideas but BF was able to direct his thoughts by identifying the questions after reading them, BF could not give answers that were not uncommon or that were rarely given by others because BF said that the solution method he used was the solution method that the teacher had used teach in class, BF is not able to develop, add, expand an idea but BF is able to solve problems in detail and can be understood by others.